From corrosion behavior to radiation response: A comprehensive biocompatibility assessment of a CoCrMo medium entropy alloy for utility in orthopedic and dental implants. (October 2022) - Gurel, S.; Nazarahari, A.; Canadinc, D.; Gerstein, G.; Maier, H.J.; Cabuk, H.; Bukulmez, T.; Cananoglu, M.; Yagci, M.B.; Toker, S.M.; Gunes, S.; Soykan, M.N.
Abstract: This paper presents a thorough biocompatibility evaluation of a CoCrMo medium entropy alloy to assess its potential to be utilized in orthopedic and dental implants. For this purpose, a wide range of systematic experiments were carried out, including static immersion, cell culture and radiation experiments. In particular, chemical biocompatibility and ion release behavior of the CoCrMo alloy were studied by carrying out static immersion experiments in artificial saliva (AS), simulated body fluid (SBF) and fetal bovine serum (FBS). Detailed analysis of the surfaces of the tested samples demonstrated that both passive oxide layer and hydroxyapatite formation occur on the CoCrMo sample surfaces immersed in AS, SBF and FBS for 28 days. The response of living cells to the CoCrMo alloy was tested utilizing cell culture experiments, and the evidence of Saos-2 cell viability and proliferation supported the static biocompatibility experiment results, indicating the potential of the CoCrMo alloy to be utilized as an orthopedic implant material. Finally, the effect of a CoCrMo implant on the actual radiation dose induced upon malignant tissue in the vicinity of the implant during a radiotherapy was evaluated by applying medical grade radiation to water phantoms circumventing CoCrMo samples. The results showed that the radiation accumulation in the tissue within the immediate vicinity of a CoCrMo implant would be a minimum, eliminating some of the undesired side effects. Overall, the results of the three different types of experiments reported in this paper have clearly demonstrated that the CoCrMo medium entropy alloy investigated in this study has significant potential to be utilized as a safe implant material in dental and orthopedic implants. Highlights: Biocompatibility of a CoCrMo medium entropy alloy was investigated. Hydroxy apatite and passive oxide layer formation was observed upon immersion. Saos-2 cell viability and proliferation was prevalent on the surface. Radiation accumulation around CoCrMo samples remained a minimum. Experiments show the potential of CoCrMo as orthopedic and dental implant material.